2002
DOI: 10.1073/pnas.022516199
|View full text |Cite
|
Sign up to set email alerts
|

The tomato Blind gene encodes a MYB transcription factor that controls the formation of lateral meristems

Abstract: The multitude of forms observed in flowering plants is largely because of their ability to establish new axes of growth during postembryonic development. This process is initiated by the formation of secondary meristems that develop into vegetative or reproductive branches. In the blind and torosa mutants of tomato, initiation of lateral meristems is blocked during shoot and inflorescence development, leading to a strong reduction in the number of lateral axes. In this study, it is shown that blind and torosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
227
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(237 citation statements)
references
References 45 publications
6
227
0
4
Order By: Relevance
“…LS, LAS, and MOC1 are orthologous genes encoding transcriptional regulators of the GRAS family (Schumacher et al, 1999;Greb et al, 2003;Li et al, 2003). BL and RAX are also orthologous genes that encode R2R3-type Myb transcription factors (Schmitz et al, 2002;Keller et al, 2006;Mü ller et al, 2006). This shows that AM formation may be regulated by a conserved mechanism in different plant species, including monocots and eudicots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LS, LAS, and MOC1 are orthologous genes encoding transcriptional regulators of the GRAS family (Schumacher et al, 1999;Greb et al, 2003;Li et al, 2003). BL and RAX are also orthologous genes that encode R2R3-type Myb transcription factors (Schmitz et al, 2002;Keller et al, 2006;Mü ller et al, 2006). This shows that AM formation may be regulated by a conserved mechanism in different plant species, including monocots and eudicots.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the defective genes in these mutants are probably involved in mechanisms that control general aspects of meristem initiation or function unless AM formation is affected as a secondary consequence of these mutations. The other class of mutants, comprising Arabidopsis thaliana lateral suppressor (las) and regulator of axillary meristem (rax) mutants, tomato (Solanum lycopersicum) lateral suppressor (ls) and blind (bl), maize (Zea mays) barren stalk1 (ba1), and rice (Oryza sativa) monoculm1 (moc1) and lax panicle1 (lax1) show AM-specific defects (Schumacher et al, 1999;Komatsu et al, 2001Komatsu et al, , 2003Ritter et al, 2002;Schmitz et al, 2002;Greb et al, 2003;Li et al, 2003;Keller et al, 2006;Mü ller et al, 2006). These AM-specific mutants can be further divided into two classes: either the mutant shows developmental specific defects or all AMs are affected regardless of the plant's developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…The NAC domain transcription factors CUC1,2,3 play a role in axillary meristem initiation in Arabidopsis, but in rice, overexpression of OsTIL1 enhances axillary meristem outgrowth rather than initiation (Vroemen et al, 2003;Hibara et al, 2006;Mao et al, 2007;Raman et al, 2008). R2 R3 Myb transcription factors RAX1,2,3/BLIND (Schmitz et al, 2002;Keller et al, 2006;Muller et al, 2006) play a role in eudicots, but a homolog in monocots has not yet been identified. Therefore, the roles of these transcription factors still need to be clarified in monocots.…”
Section: Role Of Auxin In Axillary Meristem Initiation During Vegetatmentioning
confidence: 99%
“…However, the molecular mechanisms that control branching in eudicots are not completely conserved with tiller development in grasses (Kebrom et al, 2013;Hussien et al, 2014;Waldie et al, 2014). For example, the reduced-branching mutations in the REGULATOR OF AXILLARY MERISTEMS1, REGULATOR OF AX-ILLARY MERISTEMS2, REGULATOR OF AXILLARY MERISTEMS3, and BLIND genes of Arabidopsis and tomato (Schmitz et al, 2002;Keller et al, 2006;Müller et al, 2006) are conserved in eudicots but have not been identified in monocot genomes (Keller et al, 2006;Müller et al, 2006).…”
mentioning
confidence: 99%